2008
DOI: 10.1016/j.applanim.2008.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Maternal behaviour in Mus musculus sp.: An ethological review

Abstract: In this paper, we review the scientific literature on maternal behaviour in commensal house mice and laboratory mice. Similar to other altricial species, female mice prepare a nest before parturition. Once the pups are born, nursing is the main part of maternal behaviour, and pups are weaned through a gradual non-aggressive process after about 3 weeks. Mice are social and both males and females show parental behaviour. Female mice giving birth at about the same time form communal nests, where pups are also com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
82
0
5

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(95 citation statements)
references
References 104 publications
(243 reference statements)
4
82
0
5
Order By: Relevance
“…Nesting behavior was reduced in lactating ephrin-A5 -/- females at 6 and 24 hours after providing the nesting material. Since mice are born without the ability to regulate their body temperature, the construction of the nest is important for their survival (Weber & Olsson, 2008). It is therefore not surprising that pups born to ephrin-A5 -/- females had a lower survival rate compared to those born to wild-type controls.…”
Section: Discussionmentioning
confidence: 99%
“…Nesting behavior was reduced in lactating ephrin-A5 -/- females at 6 and 24 hours after providing the nesting material. Since mice are born without the ability to regulate their body temperature, the construction of the nest is important for their survival (Weber & Olsson, 2008). It is therefore not surprising that pups born to ephrin-A5 -/- females had a lower survival rate compared to those born to wild-type controls.…”
Section: Discussionmentioning
confidence: 99%
“…Several experimental studies have shown infanticide in female mice. However, these are experimental studies conducted to observe infanticide from a behavioural ecology perspective where females with differing sexual experience are exposed to related or unrelated pups [for overview [1,27,32]; these studies do not represent normal husbandry conditions and are not applicable when addressing the question about infanticide under the current conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Though unexpected, the fact that our subjects were females (by necessity) might explain these results. Adult mice are much more likely to build nests when in company of other littermates, and females, in particular, show a high degree of nest building only during maternal phase (during pregnancy and a few days after delivery) [40]. In a study with mouse models for autism, El-Kordi et al found that only male mutants had a higher proportion of untouched nesting material and built significantly less functional nests.…”
Section: Deficits In Social and Repetitive Behaviors And Their Relevmentioning
confidence: 98%